(untitled) (International Journal of Engineering and Computer Science, 2017)
The amazing demands from social market are pushing the development of mobile communications faster than before, leading to emergence of new advanced techniques. This paper describes the need for enhancements in mobility management for current and future communication networks and the integration of these heterogeneous networks for a smooth handoff and better quality service in the context of next evolutionary step for wireless communication networks. IP based service technologies are becoming increasingly important in wireless communications. Cellular networks will be used as an access method to the Internet and other IP-based networks. The macro and micro mobility solutions for Mobile IP are analyzed and a comparative study is done among HMIP, Cellular IP and HAWAII protocols.